Structural Emergence: Architectural and Structural Design Collaboration at SOM. (12th March 2013) - Besserud, Keith; Katz, Neil; Beghini, Alessandro; Peters, Brady; De Kestelier, Xavier
Abstract At Skidmore, Owings & Merrill (SOM) there is a strong culture of collaboration between architects and engineers, and innovation in computational technologies ‐ the firm fervently embraced the computer over 50 years ago. Here a cross‐disciplinary team from SOM, architects Keith Besserud and Neil Katz and structural engineer Alessandro Beghini, describe their current work on FE algorithms and how this has informed recent projects.